2017
DOI: 10.1104/pp.17.00688
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Transcriptomes at High Resolution Using Retooled INTACT

Abstract: Isolated nuclei provide access to early steps in gene regulation involving chromatin as well as transcript production and processing. Here, we describe transfer of the isolation of nuclei from tagged specific cell types (INTACT) to the monocot rice (Oryza sativa L.). The purification of biotinylated nuclei was redesigned by replacing the outer nuclear-envelope-targeting domain of the nuclear tagging fusion (NTF) protein with an outer nuclear-envelope-anchored domain. This modified NTF was combined with codon-o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 38 publications
1
40
0
Order By: Relevance
“…The binary vector used for M. truncatula was identical to the tomato vector (Ron et al, 2014) but was constructed in a pB7WG vector containing the phosphinothricin resistance gene for plant selection and it retains the original AtACT2p promoter. The binary vector used for rice is described elsewhere (Reynoso et al, 2017). Transformation of rice was performed at UC Riverside and tomato transformation was performed at the UC Davis plant transformation facility.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…The binary vector used for M. truncatula was identical to the tomato vector (Ron et al, 2014) but was constructed in a pB7WG vector containing the phosphinothricin resistance gene for plant selection and it retains the original AtACT2p promoter. The binary vector used for rice is described elsewhere (Reynoso et al, 2017). Transformation of rice was performed at UC Riverside and tomato transformation was performed at the UC Davis plant transformation facility.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…INTACT was originally developed for the purification of nuclei from Arabidopsis root tissues, but it has been adapted and employed for genomic, epigenomic and proteomic studies of other cell types and plant species such as rice or tomato, as well as non-plant model organisms such as flies, worms and Xenopus (Deal and Henikoff 2010;Steiner et al 2012;Henry et al 2012;Amin et al 2014;Moreno-Romero et al 2016;Reynoso et al 2017;Palovaara et al 2017). Previously, we have reported the adaptation of the INTACT system for the generation of epigenome profiles of the endosperm by expressing the NTF-GFP and BirA components under the endosperm-specific PHERES1 (PHE1) promoter (Moreno-Romero et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…INTACT is a versatile tool that has been used for transcriptomic, epigenomic and proteomic studies of tissue-and celltype-specific nuclei in plants and animals (Amin et al 2014;Foley et al 2017;Henry et al 2012;Moreno-Romero et al 2017;Park et al 2016;Reynoso et al 2018a;Ron et al 2014;Steiner et al 2012). In fact, a recent publication showed that several of these -omics studies can be performed on the same pool of INTACT-isolated nuclei (Mo et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, relatively few studies have investigated the differences between nuclear, cytosolic and total transcriptomes in detail, especially in plants (see e.g. Barthelson et al 2007;Chen and van Steensel 2017;Djebali et al 2012;Bahar Halpern et al 2015;Reynoso et al 2018a;Solnestam et al 2012). Until recently, the primary reason for this has been the lack of technologies that facilitate such a comparison, particularly at the tissue or cellular level.…”
Section: Comparing Nuclear and Cellular Transcriptomesmentioning
confidence: 99%